Privatization and Regulation of Transport Infrastructure in the 1990s : Successes . . . and Bugs to Fix for the Next Mille - Estache, Antonio 1957- (The World Bank, 1999)
Learning to regulate fairly, effectively, and at arm's length may be the main challenge governments face in attracting private investment and financing to the transport sector. - Governments should increasingly be able to rely on the private sector for help supporting (and financing) the transport sector - especially infrastructure support services for which there is heavy demand - but first they must improve their regulatory tools and sort out the institutional mess surrounding the regulatory process. Some countries have put together creative restructuring models and financing designs that tap potential in the private sector. Roads will continue to need significant public funding, but there are innovative ways (including shadow tolls) to attract private financing for road maintenance and investment. Partnerships between the public and private sectors have remained largely untapped at ports and airports. To attract more private capital to the sector, regulators must know the cost of capital, know how to be fair to captive shippers, and have a better handle on demand - so they have more credibility when conflicts arise. Governments have overemphasized making deals and have generally underestimated the difficulty of taking on their new job as regulators. They are increasingly switching to contract-based regulation, to firm up the commitments of all parties involved, but are not adequately emphasizing contract design that anticipates problems and addresses unpredictable situations. This increases the risk of arbitrary regulatory rulings, which increases regulatory and political risks, which raises the expected rate of return required by potential investors. And all that makes future projects costlier or more difficult, adding to the effects of the 1998-99 financial crisis.